Recent Developments in Pharmacotherapy of Alcoholism - Soyka, M.; Lieb, M. (Pharmacopsychiatry, 2015)
Introduction: Alcohol use disorders are common, but only a small minority of patients receive adequate treatment. Cognitive-behavioural therapies, motivational enhancement interviewing and brief interventions are established treatments, but few pharmacotherapies are available.Areas Covered: This narrative focuses on the neurobiological basis of alcohol use disorders and on emerging drugs that either have recently been approved or look likely to find their way into clinical practice. To date, acamprosate and the opioid antagonist naltrexone have been approved for treatment of alcohol dependence. Recently, the mu-opioid antagonist and partial kappa agonist nalmefene was approved by the European Medicines Agency for reduction of alcohol consumption. Novel clinical approaches include drugs established for other indications such as the GABA-B receptor agonist baclofen, anticonvulsants such as topiramate and gabapentin, the partial nicotine receptor agonist varenicline, and other drugs. Developments in pharmacogenetics are discussed.Conclusions: The development of pharmaceutical agents to treat alcohol use disorders has lagged behind that of depression and schizophrenic psychosis and is hampered by an incomplete understanding of the neurobiological background. Pharmacogenetics may improve treatment in the future.
Keywords: alcohol; alcoholism; baclofen; gabapentin; nalmefene; opioid antagonists; topiramate; varenicline